Blood lactate and heat stress during training in rowers - Maciejewski, H.; Messonnier, L.; Moyen, B.; Bourdin, M. (International Journal of Sports Medicine, 2007)
The purpose of the present study was to test the hypothesis that large increases in blood lactate concentration ([La]b) and/or body temperature may occur during an endurance training on a rowing ergometer and disrupt training. The influence of an increase in air convection on the capacity to perform a prolonged exercise was also explored. Ten trained oarsmen were asked to undergo twice, in control (C) and increased air ventilation (AV) conditions, two 30-min trainings on a rowing ergometer at a work rate corresponding to 2.5 mmol · L-1 of [La]b determined during a previous incremental exercise (P2.5). Four subjects did not complete the training session in C despite a steady state in [La]b in two of them. In these four subjects, the end of the exercise was associated with the highest measured rectal temperatures (Tre, 39.4 ± 0.1 °C) and rate of perceived exertion (RPE, 17.8 ± 0.3). Regarding the six other subjects, their heart rate, oxygen uptake, RPE, Tre and water loss values were lower (p < 0.05) in AV than in C. [La]b displayed the same profile in C and AV. This study suggests that i) high body temperature may constitute a significant factor of perceived exertion and disrupt indoor training session, and ii) capacity to perform an endurance training on a rowing ergometer was improved by increasing air convection.